Energy sector enterprises in digitalization program: Its implication for open innovation - Yulia Valeeva; Marina Kalinina; Lilia Sargu; Anastasia Kulachinskaya; Svetlana Ilyashenko (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The digital economy implies structural transformation in many industries, including the energy sector, without considering the state specifics of the industry, for which full-fledged digitalization can be harmful. The aim of the study is to develop a methodology and to determine the level of digitalization in the energy sector in an intercountry context. Based on the methods of comparison and analysis, the work analyses the concept of 'digitalization' and defines the indicators applied to the assessment of digitalization. The developed methodology is based on the index method, which makes it possible to assess the rating of countries by the level of digitalization in the energy sector. The article discusses modern technological development and socio-economic aspects that determine theoretical research and the development of digitalization in the energy sector. The reasons and stages of digitalization in the energy sector are highlighted. Using the comparison method, the analysis of existing approaches to assessing the digital energy of enterprises is carried out. End-to-end technologies are highlighted, as well as their practical application at the enterprises of the energy sector. An analysis of the key areas for the development of digital energy is presented. Conclusions are made about the feasibility of developing microprograms and the main directions of digitalization are highlighted.
Keywords: 650; barriers to digitalization; digital energy; digitalization; industrial enterprises; open innovation; stages of digitalization